Pain perception in personality disorders - Spyridoula Bourtzoni; Phil Reed (PLoS ONE, 2025)
Research has focused on pain perception of individuals with Borderline Personality Disorder, but there is a lack of research regarding pain perception for other types of Personality Disorders. The present study explored associations between the perception of experimentally-induced acute pain of individuals without acute or chronic pain with Borderline, as well as Histrionic, and Schizotypal, Personality Disorders traits. The primary question of interest was whether any personality disorders were associated with altered pain perception. Fifty-two participants had pain induced by a cold-pressor task, and were evaluated for personality disorder traits. Psychophysiological perception of pain was measured using pain threshold and tolerance tests, subjective reports of pain were taken using the McGill Pain Questionnaire, and physiological aspects were measured using Galvanic Skin Response as an index of physiological arousal. The results showed significant associations between Histrionic Personality Disorder and subjective reports of the sensory aspects, and intensity, of pain, but not with psychophysiological or physiological responses (although caution is needed in interpreting the results of multiple tests). There were no significant associations regarding pain perception and Borderline, or Schizotypal, Personality Disorders. These results are preliminary, but provide novel suggestions regarding the impact of Personality Disorder on pain perception and guidance for future research has been provided.